Extraction and Characterization of Keratin from Chicken Feather Waste Biomass: A study - Sharma, Swati; Gupta, Arun; Syed Mohd Saufi, Tuan Chik; Chua, Gek Kee; Pradeep Kumar , Podde; Jayshree , Thraisingam; Malini, Subramaniam (Universiti Malaysia Pahang, 2016)
Keratins are proteins that form hard fibers, present in wool, horns and hoofs, feathers etc. The feathers consist of up to 10% of total chicken weight. Uncontrolled disposal of feathers from the poultry slaughterhouses industry is troublesome to environment. Primary purification phase is necessary for isolating the keratin from other materials. The present work was conducted to isolate the chicken feathers and to extract the keratin from processed biomass. The purification was conducted by washing with ddH2O, detergents and ether and lastly again with boiled water at (100oC). Reducing agents used were sodium sulfide and sodium sulfite. The precipitates obtained in the form of pellet were washed 2-3 times with ddH2O in order to remove foul smell and residues of sodium sulfide and HCl can be washed properly. To prepare the soluble form sodium hydroxide was added. Among the reducing agents tested Sodium sulfide showed good dissolving power as compared to others. Sodium sulfide with 0.3M and 0.5M concentrations dissolved the chicken feather efficiently. Keratin protein was dialyzed by ddH2O using cellulose membrane (12 MWCO) which retained the protein size ~12 kDa. The concentration of keratin was studied by Bradford method (1.6mg/ml) and physiochemical characterization was done by FTIR and TGA analysis. The presence of alkane, carboxylic acid, amine, thiocarbonyl groups and disulfide bond was confirmed by FTIR analysis. The purified keratin is a promising substrate for the synthesis of cosmetic and pharmaceutical products.